Associação de carboidrases e fitase em dietas valorizadas e seus efeitos sobre desempenho e qualidade dos ovos de poedeiras leves - Ferreira, C. B. (2015)
A total of 350 commercial Bovans White laying hens were used to evaluate the association of carbohydrases and phytase in enriched diets and its effects on performance and egg quality of laying hens. The experiment used a randomized design with five treatments and seven replicates. The treatments were: 1. Positive control without added enzymes and without nutrient enrichment, 2. Negative control (NC) 1 with 1.5% and 6% AME (kcal/kg) enrichment for corn and soybean meal respectively, 2% crude protein (CP) enrichment, and digestible limiting digestible amino acids plus the full matrix for the phytase enzyme; 3. NC 2 with 1.5% and 6% AME (kcal/kg) enrichment, respectively, for corn and soybean meal and 2% crude protein (CP) enrichment, and digestible limiting amino acids plus the sparse matrix for the phytase enzyme, 4. NC 1 supplemented with 100 g ton-1 carbohydrase and 30g ton-1 phytase, 5. NC 2 supplemented with 100 g ton-1 carbohydrase and 30g ton-1 phytase. According to the results, the positive control treatments, NC1 and NC2, with or without enzyme supplementation, showed guaranteed performance for feed intake, egg yield, weight, egg loss and shell quality.